Extended polymerization in ABC-stacked C70 fullerite. (February 2015) - Marques, L.; Skorokhod, Y.; Soares, R.
Abstract: This letter reports on the extended polymerization occurring in ABC -stacked C70 fullerite, which up to now was thought to occur only in the AB -stacked phase. Frustration effects on ABC close-packing of C70 molecules were believed to prevent extended polymerization based on 2 + 2 cycloaddition bonds, but here we show that an extended polymeric phase is obtained at 10 GPa and 270 °C. Its structure, obtained by Rietveld analysis of the X-ray diffraction data combined with density functional theory methods, consists of zigzag chains running within the dense hexagonal (1 0 1) pyramidal planes.